The Effectiveness of Climanopoly Game-Based Learning Media to Improving Knowledge of Climate Change in the Aged 5-6 Years in Semesta Kindergarten Semarang - Nur Santi, Ni'ma Qorina; Sugiyo Pranoto, Yuli Kurniawati (BELIA Early Childhood Education Papers, 2025)
This study aims to study and analyze the effectiveness of using climanopoly media (Climate Monopoly) in improving knowledge of climate change in children aged 5-6. The background of this study is the lack of understanding of climate change in children aged 5-6 years at Semesta Semarang Kindergarten and the location of Semesta Semarang Kindergarten is close to the toll road area so a lot of carbon dioxide gas (